Influence of Seasonal Pumping on Groundwater Sources and Flow System, Nagaoka Plain, Japan. Issue 3 (17th October 2017) - Abe, Hiroaki; Tang, Changyuan; Takeuchi, Nozomu; Kondoh, Akihiko
Abstract: Intensive groundwater development in the urban area of the Nagaoka Plain, Japan, has induced changes in the pH and saturation index of calcite in groundwater. To account for these chemical changes, it is important to determine seasonal variations of recharge and the groundwater flow system in the aquifer. This study identified the sources and flow system of groundwater in this urban area by a comprehensive method using stable isotope data and a numerical groundwater model of the Nagaoka Plain. Stable isotope evidence shows that the groundwater is recharged by meteoric water originating from low‐elevation areas rather than the mountains surrounding the plain. The water table in the study area is drawn down during the winter and recovers in the other seasons. Numerical modeling shows that discharge occurs primarily along the Shinano River during the recovery period, whereas discharge is centered in urbanized areas during the drawdown period, when a conical depression of the water table stimulates recharge from the immediate area. These results are indications of a local groundwater flow system, with its recharge area between the Shinano River and the urban areas, which is governed by intensive seasonal groundwater extraction. Abstract : Article impact statement: A comprehensive method combining isotope data and modeling explains the changes in groundwater sources and flow system of an urban aquifer.